China's Envisaged Renewable Energy Target : The Green Leap Forward - World Bank (Washington, DC, 2017)
This policy note is a summary of the findings of a joint study of the Energy Research Institute of the National Development and Reform Commission, and the World Bank. The policy note is organized as follows: the next section, 'in the shadow of king coal,' provides a brief history of the development of renewable energy (RE) in China during the last three decades, which were characterized by the dominance of coal. 'Optimizing RE targets' is dedicated to the calculation of the optimal RE solutions (share of primary energy consumption and technology mix). 'China's envisaged RE target: aiming high' focuses on the evaluation of the existing and envisaged government RE targets based on the same economic, technical, and externality assumptions used for the optimization. 'Two birds with one stone: environmental protection and industrial development' is dedicated to the comparison of the government targets and optimal solutions and the analysis of incremental costs associated with them. 'The policy fundamentals on the right track' focuses on the impact of the development of RE programs on the costs of electricity generation and how to pay for it. 'Someone has to pay!' provides high-level policy recommendations that could speed up the scale-up of RE and reduce incremental costs to society. The final section, 'toward a greener future,' provides recommendations based on the results of the study to achieve scale-up of RE at minimal cost.